Leveraging sponsorship through integrated marketing - Keller, Kevin Lane (Henry Stewart Talks, 2009)
Brand equity and brand building through the brand resonance model, The role of sponsorship and event management in brand building, Sponsorship and integrated marketing communications campaigns, How American Express developed an integrated marketing campaign to leverage their 2006 US Open tennis sponsorship